Peningkatan Prestasi Belajar Siswa Materi Cerita Wayang Melalui Strategi Active Knowledge Sharing Menggunakan Media Wayang Kelas IV Sekolah Dasar - Nur Setiowati; Okto Wijayanti; Sri Harmianto (Universitas PGRI Semarang, 2019)
The background of this research was the low achievement of the students, which revealed the number of the students who did not pass the standard of Javanese Language score was 100%. The objective of this research was to enhance the students’ achievement in puppet story material, Bima Bungkus and Nggoleki Gung Susuhe Angin through active knowledge sharing strategy using puppet media. The subjects of this research were the fourth grade students of SD Negeri Kalikidang with the number of the students were 32, which were 15 students of them were male while 17 students of them were female. This research was a classroom action research that involved two cycles. Each cycle included two meetings. The implementation of each cycle involved planning, implementing, observing and reflecting. The data collection tools used were observation sheet of teacher activity, observation sheet of students’ activity and student evaluation sheet. The students’ improvement could be seen in each cycle. The indicator of students’ learning achievement was the enhancement of learning achievement at least 75% from the number of students who passed the minimum criteria of mastery learning (KKM) of Javanese Language, which was 70. The students’ achievement in the first cycle was 70.31% whereas the second cycle was 82.45%. From the findings, it can be concluded that the learning strategy of active knowledge sharing using puppet media was able to make students became more active in the teaching process. Therefore, it enhanced the students’ achievement in puppet story material, Bima Bungkus and Nggoleki Gung Susuhe Angin at the fourth grade students of SD Negeri Kalikidang, Sokaraja Sub-distric, Banyumas District.